(untitled) (Bangladesh Journal of Animal Science, 2018)
Meat and bone meal (MBM) is a potential source of animal protein for poultry. The study was undertaken to investigate the variations in the chemical composition of MBM available in different feed markets of Chittagong, Bangladesh. Secondary data from one hundred ten different MBM samples were analyzed in triplicate for dry matter (DM), crude protein (CP), crude fiber (CF), ether extract (EE) and total ash (TA) in the Poultry Research and Training Centre laboratory of Chittagong Veterinary and Animal Sciences University, Chittagong, Bangladesh during 21st October 2014 to 2nd December 2016. Data were collected, compiled and analyzed. Results indicated that, there were wide ranges of variations in the chemical compositions for different parameters. DM varied from 91.9 to 98.7% and CP varied from 18.5 to 74.5%. Similarly, CF varied from 1.1 to 2.9% and EE varied from 7.5 to 45.0%. TA varied from 4.8 to 33.6%. There was a strong negative relationship between CP and TA (r=-0.831; R2=0.691; P<0.001). However, DM and TA were positively correlated (r=0.374; R2=0.139; P=0.003). It was concluded that, chemical composition of MBM is widely variable. Wet chemistry analysis is suggested before inclusion of MBM in the diets of dairy, poultry and pet animals. Bang. J. Anim. Sci. 2018. 47 (1): 28-34